Novel superhydrophilic poly(l-lactic acid-co-ε-caprolactone)/fibrinogen electrospun patch for rat abdominal wall reconstruction. (August 2015) - Liu, Zhang; Li, Shaojie; Su, Ling; Sun, Kang; Wu, Xujun; Wu, Feng; Huang, Weihong; Yang, Li; Tang, Jianxiong; He, Hongbing
A novel superhydrophilic hybrid scaffold was created by electrospinning a mixture of poly(l -lactic acid-co-ε-caprolactone) and formulated fibrinogen. The hybrid scaffolds possess the combined benefits of each individual component, such as moderate mechanical strength and excellent biocompatibility. In vitro studies also revealed that endothelial cells seeded on the hybrid scaffolds achieved a relatively high level of cell attachment after three days of culture and a significant increase in the proliferation rate after seven days of culture, compared with pure fibrinogen or poly(l -lactic acid-co-ε-caprolactone) scaffolds. A comparative study of hybrid and pure poly(l -lactic acid-co-ε-caprolactone) patches was performed in an abdominal wall defect model in rats. In both groups, implants degraded by six months, but muscle reconstruction was only observed in the hybrid patch group.